PERANAN THE GREEN BELT MOVEMENT DALAM UPAYA KONSERVASI HUTAN DI KENYA TAHUN 2007-2014 - Pratiwi, Ni Putu Ary; Dewi, Putu Ratih Kumala; Nugraha, A.A Bagus Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRAK Environmental issues become primary agenda in international relations. This research took a case study related to the environment and the role of non governmental organization. The case study is the role of the Green Belt Movement in efforts to conserve forests in Kenya from 2007 to 2014.The Green Belt Movement is an organization that drives grassroots society, especially rural women in Kenya for the forests conservation by planting trees. This movement originated from problems of rural women in Kenya to get firewood and water to cook. One of the causes of the scarcity of firewood is deforestation. This organization supports society to keep a sustainable environment and became a local initiative that thinks globally with regard to the principles of local empowerment of the community and for the community. Keywords : Non governmental Organization, The Green Belt Movement Kenya, Forest Conservation, Ecofeminism